2013
DOI: 10.1088/0004-6256/145/4/106
|View full text |Cite
|
Sign up to set email alerts
|

Properties of M31. Ii. A Cepheid Disk Sample Derived From the First Year of Ps1 Pandromeda Data

Abstract: We present a sample of Cepheid variable stars towards M31 based on the first year of regular M31 observations of the PS1 survey in the r P1 and i P1 filters. We describe the selection procedure for Cepheid variable stars from the overall variable source sample and develop an automatic classification scheme using Fourier decomposition and the location of the instability strip. We find 1440 fundamental mode (classical δ) Cep stars, 126 Cepheids in the first overtone mode, and 147 belonging to the Population II t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
73
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 27 publications
(73 citation statements)
references
References 55 publications
0
73
0
Order By: Relevance
“…The prewhitening of the light curve is illustrated in Figure 1 An et al (2004) found the period of this star to be 9.42 days. The photometry presented by Kodric et al (2013) results in a primary period of 9.3918(85) days and a secondary period of 6.5551(49) days. The prewhitening of the light curve is presented in Figure 2.…”
Section: J00450019+4129313 -1o/2o Type Pulsatormentioning
confidence: 87%
See 4 more Smart Citations
“…The prewhitening of the light curve is illustrated in Figure 1 An et al (2004) found the period of this star to be 9.42 days. The photometry presented by Kodric et al (2013) results in a primary period of 9.3918(85) days and a secondary period of 6.5551(49) days. The prewhitening of the light curve is presented in Figure 2.…”
Section: J00450019+4129313 -1o/2o Type Pulsatormentioning
confidence: 87%
“…The second set of light curves was presented by Kodric et al (2013). They analyzed data collected by the 1.8 m Panoramic Survey Telescope and Rapid Response System (Pan-STARRS) with the 1.4 × 10 9 pixel camera.…”
Section: Data and Methods Descriptionmentioning
confidence: 99%
See 3 more Smart Citations